Laparoscopic Approach in Large Rare Adrenal Ganglioneuroma - Kelvin Candiago; Egi Edward Manuputty; Syamsu Hudaya; Yulius Fajar Martanu; Budiawan Atmadja; Agnes Stephanie Harahap; Yosephine Gracia Susufi; Yustinus Hartanto; Ajeng Indah Pramesti (Indonesian Journal of Cancer, 2022)
Introduction: Adrenal ganglioneuroma is an extremely rare and benign tumor comprising Schwann cells and ganglion cells. Adrenal ganglioneuroma is usually hormonally silent and tends to be discovered incidentally on imaging tests. Here, we present a case of a 39-year-old man with adrenal ganglioneuroma who underwent laparoscopic left adrenalectomy.Case Presentation: a 39-year-old man was admitted to our department with left flank pain after he recovered from Covid-19. He had no symptoms of nausea, vomiting, headache, diarrhea, palpitation, or chest distress, and there was no lack of appetite or weight loss. He denied any medical conditions, such as hyperaldosteronism, hypercortisolism, and hypertension. On further examination with contrast-enhanced CT identified a hypo-isodense mass in the left adrenal gland, measuring 4.8 x 4.4 x 5.0 cm, and spotty dense calcification in the middle of the mass. All functional laboratory evolution showed negative including urinalysis and serum electrolyte. Because the non-functioning suprarenal tumor was presumed to be benign, a laparoscopic approach was planned for definitive extirpation of the left adrenal gland. CT triple-phase whole abdomen was done before the procedure which showed contrast-enhanced identified an isodense mass with 43 HU in the left adrenal gland, measuring 4.8 x 4.4 x 5.0 cm with absolute washout of 49.3% and relative washout of 30.7%. Laparoscopic left adrenalectomy was performed. The patient underwent successful laparoscopic extirpation of the left adrenal gland. The postoperative pathology revealed a 7.0 x 6.0 x 3.0 cm encapsulated tumor with a firm texture. Microscopically, the tumor showed a mixture of mature ganglion cells and fascicles of Schwann cells. Adrenocortical cells were found near the capsule.Conclusions: Even though there have been some guidelines for the diagnosis of Adrenal ganglioneuroma, pre-operative misdiagnoses are still frequent. We recommend that complete operative resection should be considered once malignancy cannot be excluded by pre-operative evaluation. Laparoscopic adrenalectomy is a reasonable option at least for tumors < or = 4.5 cm. Adrenal ganglioneuroma can be successfully excised laparoscopically with an appropriate and experienced surgeon.